Narratives and the Gift of the Future - Squire, Corinne (Narrative Matters)

(untitled) (The University of New Brunswick, 2012)
In this paper, I address the assumption that narratives work normatively, and argue instead that narratives are as important for registering particularities and differences that evade normalisation. Such singularities can be understood as moral appeals from the future. I draw on notions of deconstruction as a future-and ethics-oriented technology, to suggest that narratives can work similarly, and I give some examples from my own recent study of visual autobiographies.